The Effect of Financial Literacy, Mental Accounting, and Risk Aversion on Students’ Investment Decisions - I Gusti Ayu Dianita Martha Kamalini; I Ketut Suryanawa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Investment refers to the decision to allocate a certain amount of funds in the present with the expectation of obtaining returns in the future. Investment decisions are influenced by an individual’s knowledge, behavior, and emotions. Investors consider not only the prospects of investment instruments but also the psychological factors that shape their decisions. This study aims to empirically examine the effect of financial literacy, mental accounting, and risk aversion on students’ investment decisions. The research was conducted at the Faculty of Economics and Business, Udayana University, with a sample of 139 students selected using a census method. Data were collected using questionnaires and analyzed through multiple linear regression. The findings indicate that financial literacy and mental accounting have a positive influence on students’ investment decisions, while risk aversion has no significant effect. These results highlight the importance of financial knowledge and psychological awareness in making sound investment decisions. This study serves as a reference for students to better manage their finances and make more rational and well-planned investment choices.